Yeast Activities Involved in Carbon and Nitrogen Cycles in Antarctica - Vero, Silvana; Garmendia, Gabriela; Martinez, Adalgisa; Cavello, Ivana Alejandra; Wisniewski, Michael
Antarctica and sub-Antarctic regions are characterized by extreme conditions for life such as low temperatures and nutrient availability, high solar irradiation, and dryness; however, microorganisms from the three domains of life have been found as common inhabitants of soils and waters from those zones. Despite bacteria being the most numerous microorganisms in those habitats, a great diversity of psychrotrophic and psychrophilic yeasts have been also isolated and described. Yeasts, as chemoheterotrophic microorganisms, are involved in the recycling and mineralization of organic matter, playing an important role in carbon cycle. The range of organic substrates that they can degrade is wide. Their ability to produce extracellular hydrolytic enzymes involved in the breakdown of natural organic polymers has been well documented. Moreover, they can also use other substrates as n-alkanes or polyphenolic compounds as a sole carbon and energy source, so they could play a role in bioremediation in human-impacted areas. Most yeast obtain their energy by aerobic respiration; however, in anaerobic conditions, some of them carry out fermentation or anaerobic respiration. The use of nitrate or nitrite as the final electron acceptor provides nitrous oxide (a greenhouse gas) as an end product. Thus, those yeasts can be considered as denitrifying microorganisms playing an important role in the nitrogen cycle. Fil: Vero, Silvana. Universidad de la República. Facultad de Química; Uruguay Fil: Garmendia, Gabriela. Universidad de la República. Facultad de Química; Uruguay Fil: Martinez, Adalgisa. Universidad de la República. Facultad de Química; Uruguay Fil: Cavello, Ivana Alejandra. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata. Centro de Investigación y Desarrollo en Fermentaciones Industriales. Universidad Nacional de La Plata. Facultad de Ciencias Exactas. Centro de Investigación y Desarrollo en Fermentaciones Industriales; Argentina Fil: Wisniewski, ...